Interview Anxiety of Job Applicants in Relation to Age, Gender, and Academic Performance - Proma, Jannatul Ferdous; Baroi, Bijon; Muhammad, Noor (Jagannath University Journal of Science, 2024)
Interview anxiety is a prevalent issue among job applicants. It poses a significant threat to applicants' interview performance. Past studies suggest a substantial gap in the comprehension of the various factors that can influence the anxiety experienced by job applicants during interviews. The goal of this research was to explore the interview anxiety of male and female job applicants in relation to their age and academic performance. A personal information form along with the adapted Bangla version of the Measurement of Anxiety in Selection Interview (MASI) scale was applied to 260 job applicants selected purposively from different public universities in Dhaka city. In the present study, a cross-sectional survey design was employed and data were analyzed by using independent sample t-tests, Pearson product-moment correlation analysis, and stepwise multiple regression analysis. The results of the study indicated that females experience more anxiety in the selection interview than males. For both males and females, there was a positive correlation between age and interview anxiety, and academic performance was negatively correlated with interview anxiety. The results further revealed that, for both males and females, age and academic performance could predict interview anxiety where academic performance was the strongest predictor of interview anxiety. These findings may be useful to employers and human resource professionals concerned with these issues and to raise awareness regarding the interview anxiety of job applicants. Jagannath University Journal of Science, Volume 10, Number II, Dec. 2023, pp. 136-144